Evaluasi Sistem Informasi Akuntansi Penjualan Dan Pengendalian Internal Penerimaan Kas Pada PT. X Di Sidoarjo - Kristina Dadi Labo; Heri Toni Hendro P; Diana Zuhroh (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
A good accounting information system will be able to provide answers to any questions that arise in the future. This study aims to evaluate the sales accounting information system for internal control of cash receipts at PT.X in Sidoarjo. The method used in this study is a qualitative method with an emphasis on quality and the data collected is the result of interviews and direct observation. The results of the study show that the absence of a credit function and a collection function on credit sales can cause delays in collecting accounts receivable and defects in the employee work system so that it will disrupt the quality, quality and stability of the company.